2012
DOI: 10.4097/kjae.2012.62.4.343
|View full text |Cite
|
Sign up to set email alerts
|

The antiemetic effect of midazolam or/and ondansetron added to intravenous patient controlled analgesia in patients of pelviscopic surgery

Abstract: BackgroundWe made a comparative study on the antiemetic effect of midazolam and ondansetron added to intravenous patient-controlled analgesia (PCA) using fentanyl with gynecologic patients undergoing pelviscopic surgery.MethodsThe PCA using 20 µg/kg of fentanyl was started in all groups postoperatively. A dose of 16 mg of ondansetron was added to the PCA of group O (n = 30). A dose of 5 mg of midazolam was added to the PCA of group M (n = 30). While 16 mg of ondansetron and 5 mg of midazolam were added to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
2
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 31 publications
0
20
2
1
Order By: Relevance
“…16 In this study, the incidence of PONV in the group receiving ondansetron and midazolam added to a IV-PCA device containing fentanyl was significantly lower than that observed in the group receiving ondansetron added to the IV-PCA at PACU, 24 h Normally distributed data were analysed using analysis of variance and a post hoc Tukey test; non-normally distributed data were analysed using the Kruskal-Wallis test.…”
Section: Discussionmentioning
confidence: 63%
“…16 In this study, the incidence of PONV in the group receiving ondansetron and midazolam added to a IV-PCA device containing fentanyl was significantly lower than that observed in the group receiving ondansetron added to the IV-PCA at PACU, 24 h Normally distributed data were analysed using analysis of variance and a post hoc Tukey test; non-normally distributed data were analysed using the Kruskal-Wallis test.…”
Section: Discussionmentioning
confidence: 63%
“…Sedation scores within 3 h postoperatively were significantly lower in the metoclopramide group. On the contrary, Kim et al .,[ 17 ] showed in his trial that sedation scores were not statistically different between the groups. Makhdoom and Farid[ 21 ] compared midazolam 0.075 μg/kg alone or in combination with dexamethasone or dexamethasone alone and found no statistical differences between the groups regarding postoperative drowsiness.…”
Section: Discussionmentioning
confidence: 99%
“…They also found that the incidence of first attack of PONV was lower in group if dose was given before extubation as compared to group using the same premedication dose of midazolam. [ 16 ] Kim et al .,[ 17 ] compared the antiemetic effect of midazolam and/or ondansetron added to intravenous patient-controlled analgesia using fentanyl in gynecologic patients undergoing pelviscopic surgery. He concluded that the incidence of PONV in midazolam-ondansetron group (MO) was significantly lower than in group ondansetron (O) at postanaesthesia care unit, 24 h after recovery ( P < 0.05).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,8,9,10 Pada beberapa tahun terakhir, midazolam dilaporkan terbukti efektif sebagai profilaksis PONV setelah pembedahan strabismus pada pasien pediatrik, pembedahan bypass kardiopulmonar (CPB), pembedahan abdominal bawah dengan anestesi umum, bedah myringoplasty dan pada pasien pasca bedah yang mendapat patient controlled analgesia (PCA) menggunakan fentanyl. 11,12,13,14,15 Dengan latar belakang diatas dan mengacu pada penelitian sebelumnya maka peneliti ingin mengevaluasi efektivitas pemberian midazolam 35 µg/ kgBB intravena dibandingkan dengan ondansetron 4 mg intravena sebagai pencegahan PONV pada prosedur laparoskopi.…”
Section: Seluruhunclassified